A simplified model for estimating population-scale energy impacts of building envelope air tightening and mechanical ventilation retrofits. Issue 1 (2nd January 2016) - Logue, Jennifer M.; Turner, William J.N.; Walker, Iain S.; Singer, Brett C.
Abstract : Changing the air exchange rate of a home affects the annual thermal conditioning energy. Large-scale changes to air exchange rates of the housing stock can significantly alter the residential sector's energy consumption. However, the complexity of existing residential energy models is a barrier to the accurate quantification of the impact of policy changes on a state or national level. The Incremental Ventilation Energy (IVE) model introduced here combines the output of simple air exchange models with a limited set of housing characteristics to estimate the associated change in energy demand of homes. The IVE model was designed specifically to enable modellers to use existing databases of housing characteristics to determine the impact of ventilation policy change on a population scale. The IVE model estimates of energy change when applied to US homes with limited parameterization are shown to be comparable to the estimates of a well-validated, complex residential energy model.